2022
DOI: 10.1002/ags3.12548
|View full text |Cite
|
Sign up to set email alerts
|

Essential updates 2020/2021: Colorectal diseases (benign)—Current topics in the surgical and medical treatment of benign colorectal diseases

Abstract: The development of new drugs for inflammatory bowel disease (IBD) is remarkable, and treatment strategies using multiple agents and various techniques are required; however, the treatment strategy is likely to be complex. Therefore, appropriate evaluation of traditional surgical treatment strategies and accurate knowledge of the efficacy and limitations of novel treatments are required. Total infectious complications were found to be associated with the use of corticosteroids and anti‐tumor necrosis factor‐α a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…Preoperative steroid dosing, high stoma output, and the presence of malignant tumors were also noted by studies as potential risk factors. Kitahara et al [13] reported an association between a lowered corticosteroid dose a month prior to surgery and an increased risk of SOO, but this is also a common guideline for medically refractory UC preoperatively and may simply reflect the risk of patients with worsening UC [22]. Nonetheless, Kameyama et al [10] found that the perioperative steroid dose did not affect SBO incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative steroid dosing, high stoma output, and the presence of malignant tumors were also noted by studies as potential risk factors. Kitahara et al [13] reported an association between a lowered corticosteroid dose a month prior to surgery and an increased risk of SOO, but this is also a common guideline for medically refractory UC preoperatively and may simply reflect the risk of patients with worsening UC [22]. Nonetheless, Kameyama et al [10] found that the perioperative steroid dose did not affect SBO incidence.…”
Section: Discussionmentioning
confidence: 99%
“…15 From a primary care perspective, early recognition, along with its extra-articular manifestations, can lead to faster time to treatment and better health outcomes, in addition to preserved joint functionality. [16][17][18] IIDs are also used in chronic conditions of the bowels [19][20][21] (eg, Crohn's disease, ulcerated colitis, diverticulitis) as well as for antirejection therapy 22 when organ transplants or grafts have been used as they suppress the autoimmune destruction. These medicines are important because they provide a lifeline towards functional mobility and improves the quality of life 23 24 for patients by relieving their pain as well as retarding disease progression.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…IIDs are also used in chronic conditions of the bowels19–21 (eg, Crohn’s disease, ulcerated colitis, diverticulitis) as well as for antirejection therapy22 when organ transplants or grafts have been used as they suppress the autoimmune destruction. These medicines are important because they provide a lifeline towards functional mobility and improves the quality of life23 24 for patients by relieving their pain as well as retarding disease progression.…”
Section: Introductionmentioning
confidence: 99%